PALEOGEOGRAPHIC SETTINGS AND TECTONIC DEFORMATIONS OF THE BARENTS SEA CONTINENTAL MARGIN IN THE CENOZOIC - Shipilov E.V.; Golubev V.A.; Tyuremnov V.A.; Glaznev V.N. (My University, 2006)
The Barents Sea continental margin (hereafter, Barents margin) differs from other passive margins by the most extensive shelf, the giant thickness of sedimentary rocks in basins and troughs, and its unique tectonic position. The outer, almost rectangular promontory of the Barents margin juts out into its deepwater western and northern framing, identified as the Norwegian–Greenland and Eurasia basins, respectively. In this regard, the continental margin is affected by two, mutually perpendicular spreading zones (Knipovich and Gakkel ridges).
Keywords: PALEOGEOGRAPHIC SETTINGS; TECTONIC DEFORMATIONS; BARENTS SEA; CONTINENTAL MARGIN